2020
DOI: 10.1016/j.jbef.2020.100403
|View full text |Cite
|
Sign up to set email alerts
|

The impact of Coronavirus (COVID-19) outbreak on faith-based investments: An original analysis

Abstract: This paper examines the rapid spread of Coronavirus (COVID-19) and its short-term impact on the Shariah-compliant UK Dow Jones market index to capture the dynamic behavior of stock returns at economy and industry levels. Using daily data over the period January 20 to May 20 and ten UK industrial sector groupings, the findings suggest a strong and statistically significant relationship between the COVID-19 pandemic and the performance of the conventional stock market index. The findings also suggest that the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
82
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(97 citation statements)
references
References 104 publications
(116 reference statements)
12
82
0
3
Order By: Relevance
“…However, negative COVID-19 case news (such as the increase in the number of cases) has a negative and statistically significant effect on all sectoral stock returns in conventional financial markets. This result is similar to Zhang et al (2020), Al-Awadhi et al (2020, Sherif (2020) and Baig et al (2021).…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…However, negative COVID-19 case news (such as the increase in the number of cases) has a negative and statistically significant effect on all sectoral stock returns in conventional financial markets. This result is similar to Zhang et al (2020), Al-Awadhi et al (2020, Sherif (2020) and Baig et al (2021).…”
Section: Resultssupporting
confidence: 84%
“…In general, the COVID-19 outbreak causes volatility increases in the world's financial markets due to the increasing ambiguity. Sherif (2020) examined the effect of the spread rate of coronavirus on conventional and Islamic stock markets in the U.K. According to the results, while the spread rate of coronavirus is statistically significant and strongly negative in conventional stock markets, this relationship is negative but statistically insignificant in Islamic stock markets.…”
Section: Literature Examining the Effect Of Investor Sensitivity On Financial Markets During The Covid-19 Outbreakmentioning
confidence: 99%
“…Robiyanto, (2018) found that gold can serve as a safe haven asset for sharia stocks in Indonesia at thet extreme shocks occur in the Indonesian stock market. Sherif, M. (2020) found a strong and statistically significant relationship between the COVID-19 pandemic and the performance of the conventional stock market index. Vol.…”
Section: Introductionmentioning
confidence: 88%
“…During the last four decades, many sharia-compliant financial products and have been introduced all around the globe by Islamic financial institutions [69-71 products have been introduced in areas of consumer finance, investment banking, ing of poor and needy, venture capital and SME financing [72,73]. These produ services offered by the Islamic financial institutions are equity-based modes of fin such as Musharakah, Diminishing Musharaka and Mudrabaha, and asset-backed fin such as Murabaha, Ijarah, Istisna, Salam and Istisna [74,75]. Some other popular f services include Qardh-Al-Hasan, Bay-Al-Sarf and Agency.…”
Section: Research Framework: the Four-stage Economic Impact Of The Covid-19 Pandemicmentioning
confidence: 99%